IMPLEMENTASI MEDIA MAJALAH CERITA SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 3 MIN 10 NGAWI - Shiti Khoyrunnissa; Djoko Hari Supriyanto; Sofyan Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
This study aims to describe the impact of implementing children's story magazine media in class 3 learning at MIN 10 Ngawi. The method used in this research is descriptive method and uses a qualitative research approach. The technique used in this research is the technique of observation, interviews, documentation with data collectors, observation guides, interviews and field notes. The results of data analysis showed that the learning media of children's story magazines can improve student learning outcomes, it can be seen from the learning outcomes before and after using children's story magazine learning media. Before using the children's story magazine media, the average grade 3 MIN 10 Ngawi students was 64, after using the children's story magazine learning media the average grade 3 MIN 10 Ngawi students was 78.